Solvent-pore interactions in the Eagle Ford shale formation. (15th February 2019) - DiStefano, Victoria H.; McFarlane, Joanna; Stack, Andrew G.; Perfect, Edmund; Mildner, David F.R.; Bleuel, Markus; Chipera, Steve J.; Littrell, Kenneth C.; Cheshire, Michael C.; Manz, Katherine E.; Anovitz, Lawrence M.
Abstract: The effect of solvent extraction on pore space was examined on a suite of samples from the Eagle Ford Shale Formation with varying lithologies and maturities. Several solvents ─toluene, cyclohexane, methanol, dichloromethane, and hydrochloric acid─ were contacted with shale samples, extracting the compatible organic matter. The porosity in these extracted shale samples was compared to unmodified samples. The amount and type of organic matter extracted were determined using Gas Chromatography ─ Mass Spectrometry, and the porosity was determined by (Ultra) Small Angle Neutron Scattering. Mostly alkanes and aromatics were detected in the extracts, but other portions of bitumen may also have been present. Only higher molecular weight alkanes were extracted with hydrochloric acid, suggesting that physical dissolution of carbonate minerals may have liberated this portion of organic matter and the solvent was not able to penetrate the bitumen and kerogen to extract the lower molecular weight alkanes. Additionally, a decrease in porosity with extraction was observed and attributed to a dominant mechanism of kerogen swelling due to kerogen-solvent interaction.